Legal Regulation of Socially-Oriented Legal Eechnique Reglamentación jurídica de la técnica jurídica de orientación social - Khorin, Alexander N.; Potanina, Yulia M.; Brovkin, Alexander V. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT The authors defined conceptual provisions of the modern classification and specification of legal technologies. The legal tools of law enforcement technology are investigated, its concept and structure are revealed, typologies of law enforcement and law enforcement technology are defined; the forms of expression of law enforcement technology are investigated; the features of the use of law enforcement technology in various types of legal activity are revealed; the author's model of law enforcement technology of arbitration proceedings is developed; the problems of law enforcement monitoring are analyzed. The authors have proposed the ways of using judicial practice in law enforcement monitoring. RESUMEN Los autores definieron las disposiciones conceptuales de la moderna clasificación y especificación de las tecnologías jurídicas. Se investigan los instrumentos jurídicos de la tecnología de aplicación de la ley, se revelan su concepto y estructura, se definen las tipologías de la aplicación de la ley y la tecnología de aplicación de la ley; se investigan las formas de expresión de la tecnología de aplicación de la ley; se revelan las características del uso de la tecnología de aplicación de la ley en diversos tipos de actividad jurídica; se desarrolla el modelo de autor de tecnología de aplicación de la ley en los procedimientos de la cotidianidad; se analizan los problemas de la vigilancia de la aplicación de la ley. Los autores han propuesto las formas de utilizar la práctica judicial en la vigilancia de la aplicación de la ley.